Spanish‐speaking Mexican‐American parents' experiences while navigating the dental care system for their children. (3rd January 2022) - Lopez, Andrea; Hoeft, Kristin S.; Guerra, Claudia; Barker, Judith C.; Chung, Lisa H.; Burke, Nancy J.
Abstract: Objectives: The purpose of this study is to describe Mexican‐American parents' experiences navigating the dental care system for their children. Methods: Thirty in‐depth qualitative interviews were conducted with Spanish‐speaking caregivers of young children in an urban county of Northern California, asking about their experiences navigating dental care for their children. Interviews were digitally recorded, translated, transcribed, coded, and analyzed using standard qualitative procedures. Results: Caregivers reported challenges that highlight how various aspects of navigating the health care system are elemental to oral health literacy. These included making appointments, finding a provider they trust, using their dental insurance, and communicating with the dental care provider. Conclusions: When addressing oral health literacy, it is important to consider the navigational components to improve children's oral health literacy.